2020
DOI: 10.1371/journal.pone.0230336
|View full text |Cite
|
Sign up to set email alerts
|

Association between preoperative levels of 25-hydroxyvitamin D and hospital-acquired infections after hepatobiliary surgery: A prospective study in a third-level hospital

Abstract: Introduction Evidence implicates vitamin D deficiency in poorer outcomes and increased susceptibility to hospital-acquired infections (HAIs). This study examined the association between serum vitamin D levels and HAIs in a population of hepatobiliary surgery patients. Methods Participants in this prospective analytical observational study were patients who underwent hepatobiliary surgery in a tertiary hospital in Aragon, Spain, between February 2018 and March 2019. Vitamin D concentrations were measured at adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
0
16
1
3
Order By: Relevance
“…Laviano et. al revealed that preoperative 25-OH vitamin D levels were not only related with development of hospital acquired infections but also with Clavien-Dindo scale of postoperative complications(32). In contrast to their results, we observed no association between Clavien-Dindo scale and 25-OH vitamin D levels in our study.…”
contrasting
confidence: 99%
“…Laviano et. al revealed that preoperative 25-OH vitamin D levels were not only related with development of hospital acquired infections but also with Clavien-Dindo scale of postoperative complications(32). In contrast to their results, we observed no association between Clavien-Dindo scale and 25-OH vitamin D levels in our study.…”
contrasting
confidence: 99%
“…Vitamin D supplementation to raise serum 25(OH)D concentrations can help reduce hospitalassociated infections [131]. Concentrations of at least 40-50 ng/mL (100-125 nmol/L) are indicated on the basis of observational studies [132,133]. During the COVID-19 epidemic, all people in the hospital, including patients and staff, should take vitamin D supplements to raise 25(OH)D concentrations as an important step in preventing infection and spread.…”
Section: Hospital-acquired Infectionsmentioning
confidence: 99%
“…Vitamin D supplementation to raise serum 25(OH)D concentrations can help reduce hospitalassociated infections [131]. Concentrations at least 40-50 ng/ml (100-125 nmol/l) are indicated on the basis of observational studies [132], [133]. During the COVID-19 epidemic, all people in the hospital, including patients and staff, should take vitamin D supplements to raise 25(OH)D concentrations as an important step in preventing infection and spread.…”
Section: Recommendations 41 Hospital-acquired Infectionsmentioning
confidence: 99%